2011
DOI: 10.1016/j.amjcard.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Medial Elastic Fiber Loss in Acute Ascending Aortic Dissection

Abstract: The cause of acute aortic dissection continues to be debated. One school of thought suggests that underlying aortic medial cystic necrosis is the common denominator. The purpose of the present study was to determine if there was loss and, if so, how much loss of medial elastic fibers in the ascending aorta in patients with acute aortic dissection with the entrance tear in the ascending aorta. We examined operatively excised ascending aortas in 69 patients having acute dissection with tears in the ascending aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 36 publications
2
18
1
Order By: Relevance
“…The morphology of elastic fibers serves as a good marker of chronic aortic remodeling, such as replacement with fibrous tissue and deposits of mucoid material, and are easily discernable and the grading of elastic fiber loss is highly reproducible. This is in contrast to acute type A dissection, where abnormal ascending aortic elastic fibers uncommonly precede acute dissection (10,11). Supplement Figure 1 shows the frequency of elastic fiber degradation in elective TAA with regards to S100A12 protein expression.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The morphology of elastic fibers serves as a good marker of chronic aortic remodeling, such as replacement with fibrous tissue and deposits of mucoid material, and are easily discernable and the grading of elastic fiber loss is highly reproducible. This is in contrast to acute type A dissection, where abnormal ascending aortic elastic fibers uncommonly precede acute dissection (10,11). Supplement Figure 1 shows the frequency of elastic fiber degradation in elective TAA with regards to S100A12 protein expression.…”
Section: Resultsmentioning
confidence: 84%
“…However, it remains unknown if apoptosis of medial smooth muscle cells occurs prior to dissection as a primary event leading to weakening and rupture of the aortic wall, or if alternatively as suggest by Roberts et al the intraluminal arterial pressure in the false luminal channel compresses the adjacent media and induces cell death after , not before acute dissection (11). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other studies have demonstrated the lack of correlations between aortic diameter and degree of medial degeneration in the aortic wall of patients with BAV 62 as well as between the degree of elastic fiber fragmentation and the occurrence of acute dissection. 63 Hence, other important unanswered questions emerge: does the aortic diameter need to be integrated into a more complex system of stratification including other risk markers, so that its relative weight in the decision-making process can vary case by case according to other prognostic factors? And what should those other risk markers be (Table 1)?…”
Section: Bav-associated Aortopathymentioning
confidence: 99%
“…In this perspective, classical histology might be not reliable as a metric of aortopathy severity: for example, Roberts et al [7] reported that severe rarefaction of medial elastic fibres was rarely associated with acute type A aortic dissection. Moreover, Bechtel's score includes features of both medial degeneration and atherosclerosis, which may be misleading [8].…”
mentioning
confidence: 99%